BUDIDAYA TEBU PADA LAHAN KERING BERIKLIM BASAH SUATU USAHA UNTUK MEMPRODUKSI ALTERNATIF PEMANIS - SUDIATSO, SUGENG (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 1995)
The trials of cultivation of sugar cane on wet climate of rainfed area was carried out at Bogor (belong to climattic A according to Schmidt and Fergusson, 1957) from 1991 to 1996. The aim of the experiments to get the cultivation varieties of sugar cane which has high total sugar content after 6 months, either plant cane or the first rattooned. Several cultivars of PS87, produced by P3GI, were tested. The experiment consisted of plant density, date of planting kind of cultivar and level of potassium fertilizers. The result showed that the PS87-22704 cultivar and PS58 variety (as a control) produced the high total-sugar content (15.64% and 15.89%).